Kode Etik Notaris dalam Mempromosikan Diri Melalu Media Elektronik - Tri Nadia Samuel Paranna (CV Rewang Rencang, 2025)
The regulation of the code of ethics for advocates, particularly regarding violations related to self-promotion through electronic media. The rapid development of information technology has opened up new opportunities for advocates to promote their legal services, but it often leads to ethical breaches within the legal profession. This research aims to analyze the ethical code provisions concerning advocates’ self-promotional behavior and its legal implications. The method used is normative juridical, with a statutory approach and analysis of decisions by the Honorary Council of the Indonesian Advocates Association (PERADI). The findings indicate that excessive self-promotion through electronic media can be classified as a violation of the code of ethics, as it contradicts the principles of dignity, honesty, and professional responsibility. Therefore, there is a need for strengthened supervision and updated ethical regulations to adapt to the growing use of digital communication technologies.